Examination of Efficiency and Sufficiency of Salt-Pack Curing Method - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2011)
Conservation defects affect leather quality adversely and cause important economic losses. Therefore, the goal of this study was to evaluate hide quality by comparing important parameters of salt-pack cured hides and determine efficiency and sufficiency of the curing method in the areas both with and without salt crystals present on the hides. The areas with and without salt crystals on the salt-pack cured hide samples, (collected from different tanneries in the Leather Organized Tannery Region, Tuzla-Istanbul-Turkey), were examined in terms of pH values, moisture and ash contents, brine saturations, total mesophile, proteolytic and lipolytic mesophile bacterial numbers. The pH values of the both areas of all the hide samples (6.3-7.4) were found to be optimum for bacterial growth. Moisture contents of the areas without salt crystals present on the hide samples (42-57%) were found to be higher than the areas with salt crystals present (31-47%). Ash contents and salt saturations of both types of area of all the hide samples (21-36% and 100% respectively) were found to be the same as standard values. Although the hides were salt-pack cured, high numbers of mesophile, proteolytic and lipolytic mesophile bacteria were isolated from both areas of the hides. Mean values of the mesophile (2 x 10(8) c.f.u./g) and lipolytic mesophile (1.7 x 10(7) c.f.u./g) bacterial numbers of the areas without salt crystals present on the hide samples were found to be higher than the areas with salt crystals. However, mean values of the proteolytic bacterial numbers were found to be similar for the both areas (1 x 10(7) c.f.u./g, 1.5 x 10(7) c.f.u./g). As a conclusion, due to an inadequately applied salt-pack curing process, this method was not a satisfactory method to prevent bacterial proliferation on hides. Hence, the traditional salt-pack curing method should be modified to improve the counter bacterial effect.
Keywords: CURED CATTLE HIDES; BACTERIAL-POPULATIONS; HALOPHILIC BACTERIA; QUALITY; LEATHER; PRESERVATION; CHLORIDE